Target and science visibility of the solar-terrestrial observer for the response of the magnetosphere (STORM) global imaging mission concept - Murphy, Kyle R.; Shoemaker, Michael A.; Sibeck, David G.; Schiff, Conrad; Connor, Hyunju; Porter, Fredrick S.; Zesta, Eftyhia (Frontiers in Astronomy and Space Sciences, 2024)
Imaging missions in Earth Science, Heliophysics, and Astrophysics have made fundamental advancements in science and have helped to further our understanding of our natural environment.Here we review the Solar-Terrestrial Observer for the Response of the Magnetosphere (STORM) mission concept, a global solar wind-magnetosphere imaging mission and investigate how often STORM can observe and image its key science targets; the magnetopause, ring current, and auroral oval. We introduce a novel analysis which defines STORM's plasma targets as discrete sample points in space, these points are collectively called point groups. These point groups are used in conjunction with fields-of-view of STORM's imagers to quantify target visibility, how often the mission can observe each of its targets. The target visibility is combined with a statistical investigation of historical solar wind and geomagnetic data, and a k-folds/Monte Carlo analysis to quantify STORM's science visibility. That is how often specific targets can be observed during elevated solar wind and geomagnetic conditions such that detailed science investigations can be completed to address STORM's science objectives. This analysis is further expanded to potential dual-spacecraft mission configurations to determine the nominal inter-orbit phasing which maximizes target and science visibility. Overall, we find that the target and science visibility of a single spacecraft mission is large, in the 100s and 1000s of hours/events, while the target and science visibility peak for a dual-spacecraft mission where the two spacecraft are ~85 ○ out of phase.